Heterogeneous beliefs in macroeconomic growth prospects and the carry risk premium - Park, Sunjin (Journal of Banking & Finance, 2022)
To understand macroeconomic risks underlying currency carry trades, I propose exploiting rich source of information from analysts’ economic growth forecasts. Specifically, I obtain measures of global growth prospects from the cross-analyst distribution of real GDP growth forecasts. I find that the global measure of skewness in forecasts negatively predicts returns both for the G10 carry and for the carry based on a wide range of currencies. The global skewness measure is found to play a more robust role compared to the global expected growth or dispersion measure. Using a model of heterogeneous beliefs, I illustrate that the consumption risk of the unbiased agent can increase because of the presence of a pessimist, who negatively skews the forecast distribution. The additional consumption risk translates to higher currency risk, introducing a source of the carry risk premium.